Pengaruh Video Review Skincare Ms Glow terhadap Minat Beli Masyarakat - Alya Aulia; Zulfebriges (Bandung Conference Series: Communication Management, 2023)
Abstract. dr. Richard Lee is an Indonesian doctor who is a the ability and knowledge possessed, by keeping abreast of current technological developments, dr. Richard Lee finally created YouTube to review skincare products. Products reviewed is MS Glow is a skincare or beauty product brand has achieved the top. Based on this phenomenon, the problem in this research is formulated as follows: (1) Is there an effect of the orientation of the MS Glow skincare video review on buying interest on YouTube Channel subscribers dr. Richard Lee? (2) Is there any influence on the interpretation of the MS Glow skincare video review on buying interest on YouTube Channel subscribers dr. Richard Lee? (3) Is there any effect of evaluating the MS Glow skincare video review on preferential buying interest on dr. Richard Lee? (4) Is there any effect of the MS Glow skincare video review summary on explorative buying interest on dr. Richard Lee?. Researcher using parcial analysis technique using a quantitative approach. Selected population in this study is the YouTube Channel subscriber dr. Richard Lee as much as 2.96 million. Using the slovin formula, the samples obtained were 100 people. The results of this study are: The results of the t-test (partial) show that the significance value of the influence of Video Review (X) on Purchase Interest (Y) is 0.026 <0.05. There is a strong influence between the reviews of MS Glow skincare products (X) on the buying interest of dr. Richard Lee (Y)Keywords: Video Review, YouTube, Subscriber, Buying Interest Abstrak. dr. Richard Lee adalah seorang dokter Indonesia yang memiliki kemampuan dan ilmu yang dimiliki, dengan mengikuti perkembangan teknologi saat ini, dr. Richard Lee akhirnya membuat YouTube untuk mengulas produk perawatan kulit. Produk yang diulas adalah MS Glow merupakan brand produk perawatan kulit atau kecantikan yang telah mencapai puncaknya. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Ada pengaruh orientasi video review MS Glow skincare terhadap minat beli pada subscriber YouTube Channel dr. Richard Lee? (2) Ada pengaruh interpretasi video review MS Glow skincare terhadap minat beli pada subscriber YouTube Channel dr. Richard Lee? (3) Apakah ada pengaruh penilaian video review MS Glow skincare terhadap minat beli preferensial pada dr. Richard Lee? (4) Apakah ada pengaruh video ringkasan review MS Glow skincare terhadap minat beli eksploratif pada dr. Richard Lee?. Peneliti menggunakan teknik analisis parsial dengan menggunakan pendekatan kuantitatif. Populasi yang dipilih dalam penelitian ini adalah subscriber YouTube Channel dr. Richard Lee sebanyak 2,96 juta. Dengan menggunakan rumus slovin didapatkan sampel sebanyak 100 orang. Hasil penelitian ini adalah: Hasil uji t (parsial) menunjukkan bahwa nilai signifikan pengaruh Video Review (X) terhadap Minat Beli (Y) adalah 0,026 < 0,05. Terdapat pengaruh yang kuat antara review produk skincare MS Glow (X) terhadap minat beli dr. Richard Lee (Y) Kata Kunci: Review Video, YouTube, Subscriber, Minat Beli.